Physicians’ Knowledge and Attitudes Regarding Point-of-Care Pharmacogenetic Testing: A Hospital-Based Cross-Sectional Study - Muflih S; Alshogran OY; Al-Azzam S; Al-Taani G; Khader YS (Dove Medical Press, 2021)
Suhaib Muflih,1 Osama Y Alshogran,1 Sayer Al-Azzam,1 Ghaith Al-Taani,2 Yousef S Khader3 1Department of Clinical Pharmacy, Jordan University of Science and Technology, Irbid, 22110, Jordan; 2Department of Pharmacy Practice, Yarmouk University, Irbid, Jordan; 3Department of Public Health, Jordan University of Science and Technology, Irbid, 22110, JordanCorrespondence: Suhaib MuflihFaculty of Pharmacy, Jordan University of Science and Technology, Irbid, 22110, JordanTel +962-79-7868603Email smmuflih@just.edu.joIntroduction: Pharmacogenetic testing (PGx) is a diagnostic technique used by physicians to determine the possible reactions of patients to drug treatment on the basis of their genetic makeup. The aim of this study was to determine the impact of physicians’ awareness, attitudes, and sociodemographics on the adoption of point-of-care (POC) PGx testing as a diagnostic method, as well as the impact of their knowledge, attitudes, and sociodemographics on its adoption.Methods: A cross-sectional survey of 200 physicians and medical trainees working at the Clinics of King Abdullah University Hospital in Jordan was performed. Data on sociodemographics, knowledge and attitudes concerning PGx testing, genetic information sources, and barriers to POC-PGx testing adoption were gathered.Results: Participants’ perceived knowledge of the role of PGx testing in therapeutic decision-making was rated as “Excellent” (1.9%), “Very Good” (19.4%), “Good” (34.4%), “Fair” (32.5%), and “Poor” (11.9%). Physicians’ actual knowledge of PGx testing was adequate (mean=3.56 out of 7, SD=1.2), but their attitudes were generally favorable (mean=3.64 out of 5.00, SD=0.52). According to Rogers’ theory, many variables (eg, perceived need, relative advantage, compatibility) had a significant impact on physicians’ willingness to endorse POC-PGx testing.Discussion: The majority of physicians stated that they were unaware of PGx testing. Physicians’ perceived knowledge of POC-PGx testing, however, was higher than those who participated in other studies. Participants were optimistic about the future benefits of PGx testing in prescribing effective medications and reducing potential side effects, which were consistent with previous studies. Physicians’ willingness to accept and implement POC-PGx testing was hampered by a lack of PGx expertise, as well as concerns about patient confidentiality, employability, and insurability. More training and genetic courses are needed, according to the majority of participants.Keywords: pharmacogenetics, physicians, knowledge, attitudes, point-of-care, Rogers theory